2012
DOI: 10.1364/ol.37.000629
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of a passive all-fiber Q-switched erbium- and samarium-doped laser

Abstract: Self-Q-switched operation of the all-fiber laser using erbium and samarium fibers in the cavity is realized experimentally. This passively Q-switched all-fiber laser produces very stable pulses with energy of 142 nJ and duration of 450 ns. The experimental results were well reproduced by the results obtained through the numerical integration of a rate-equations model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…F IBER saturable absorbers (FSAs) have been widely studied for passive Q-switching of various rare earth doped fiber lasers [1]- [4]. As absorption bands of Tm ions overlap with the emission bands of Yb-doped fiber laser and Er-doped fiber laser [5], Tm-doped fiber and Tm-Ho codoped fiber have been used as FSAs for passive Q-switching of Yb-doped and Er-doped fiber lasers [6]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…F IBER saturable absorbers (FSAs) have been widely studied for passive Q-switching of various rare earth doped fiber lasers [1]- [4]. As absorption bands of Tm ions overlap with the emission bands of Yb-doped fiber laser and Er-doped fiber laser [5], Tm-doped fiber and Tm-Ho codoped fiber have been used as FSAs for passive Q-switching of Yb-doped and Er-doped fiber lasers [6]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Das et al [27] demonstrated Samarium-doped fiber as SA for ytterbium-doped fiber lasers which successfully generated pulses in the 1 µm range. With a fast response time of 5 ns, Samarium oxide (Sm2O3) has excellent nonlinear absorption ability of 33% in a 1.5 µm regime [28,29]. Its thin film is reported to have high chemical and thermal stability, making it efficient for pulsed laser generation due to its ability to withstand high power illumination from laser pumps [30].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve short laser pulses, Q-switching is performed by passive and active techniques. The passive Q-switching is based on the use of a saturable absorber such as fiber with graphene or carbon nanotube deposits [7][8][9][10][11] and un-pumped segments of active fiber [12,13]. In this case, the repetition rate of the generated pulses is determined by the pump power which limits the controlling of the laser pulses characteristics and the output power reached.…”
Section: Introductionmentioning
confidence: 99%